Diet-Mediated Pheromones and Signature Mixtures Can Enforce Signal Reliability - Henneken, Jessica; Goodger, Jason Q. D.; Jones, Therésa M.; Elgar, Mark A. (Frontiers in Ecology and Evolution, 2017)
Diet is arguably the most significant environmental factor shaping chemical signals in animals. In rare cases, dietary components are converted directly into pheromones or signature mixtures but more generally variation in an individual’s diet influences their overall condition and thus capacity to synthesise the signal. Typically, diet is variable between individuals of the same species and this can lead to variation in signals. This variation presents specific challenges to receivers, who must be able to recognise and respond to a greater range of signals. However, such variation might also provide the receiver with key information about the signaller, allowing them to respond to the signal advantageously. Here we investigate how dietary-mediated pheromones and signature mixtures can provide the receiver with reliable information about the signaller, ultimately benefiting the receiver in a way not achievable by a static signal.